The Konstanz Seminar on Monetary Theory and Policy at Thirty - Michele Fratianni; Jürgen von Hagen (Rheinische Friedrich-Wilhelms-Universität Bonn, Zentrum für Europäische Integrationsforschung (ZEI), 2001)
Founded by the late Karl Brunner in 1970, the Konstanz Seminar celebrated its thirtieth anniversary in 1999. Brunner started the Seminar with two objectives, to close the gap in the quality of research and teaching of economics between the United States and Europe, Germany and Switzerland in particular, and to provide an alternative to the dominant Keynesian paradigm to European monetary policy makers. Thirty years ago the Konstanz Seminar was at the fringe of the economics profession; today it is part of the mainstream. This paper reviews the academic and policy accomplishments of the Konstanz Seminar.
Keywords: 330; Geldtheorie; Geldpolitik; Dogmengeschichte; Theorie